2014
DOI: 10.1056/nejmsa1404026
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Health Care Spending and Quality 4 Years into Global Payment

Abstract: BACKGROUND Spending and quality under global budgets remain unknown beyond 2 years. We evaluated spending and quality measures during the first 4 years of the Blue Cross Blue Shield of Massachusetts Alternative Quality Contract (AQC). METHODS We compared spending and quality among enrollees whose physician organizations entered the AQC from 2009 through 2012 with those among persons in control states. We studied spending changes according to year, category of service, site of care, experience managing risk c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
142
2
3

Year Published

2015
2015
2017
2017

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 191 publications
(153 citation statements)
references
References 26 publications
5
142
2
3
Order By: Relevance
“…They found that jointly incentivizing physicians and patients was more successful at reducing cholesterol levels than offering incentives to either physicians or patients alone. The same logic broadly applies to the shared savings offered to providers who collaborate in accountable care organizations (14) (see the section titled Part 2: Incentives in the Affordable Care Act), under which groups of providers share the same set of incentives for quality and efficiency (93).…”
Section: Introductionmentioning
confidence: 99%
“…They found that jointly incentivizing physicians and patients was more successful at reducing cholesterol levels than offering incentives to either physicians or patients alone. The same logic broadly applies to the shared savings offered to providers who collaborate in accountable care organizations (14) (see the section titled Part 2: Incentives in the Affordable Care Act), under which groups of providers share the same set of incentives for quality and efficiency (93).…”
Section: Introductionmentioning
confidence: 99%
“…35 Although the costs of the two chemotherapy regimens themselves are nearly identical, the differences in subsequent hospital-based care dwarf the direct costs of treatment. Drug costs for these two regimens (not including office visits, administration charges, etc.)…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, there is no evidence of the effectiveness of any single payment model as a tool for reducing overuse specifically. At a high level, however, the evidence suggests that risk sharing reduces use and total cost, [55][56][57] whereas pay for performance has had a much more mixed record of success. 58 A critical question for the ongoing research on global and bundled payment initiatives (eg, Medicare's Accountable Care Organizations Shared Savings Program and Bundled Payment for Care Initiative) is whether these approaches, which effectively encourage reduction in costs regardless of value, have a disproportionate effect on overuse.…”
Section: Opportunities For Reformmentioning
confidence: 99%